Mapping of Hydro Power Energy Potential for Energy Intervention Solution in Malaysia - Bohari, N.; Abidin, W.A.W.Z; Salleh, D.N.S.A; Anyi, M. (ENCON 2013, 2013)
This paper presents the overview study of hydro potential sites in Malaysia with additional review on existing project development in Malaysia. As known widely, Malaysia is gifted with hilly areas and vast water resources which promise to give high potential in hydro power. Therefore, a study on suitable sites for hydro power development is required and this is done by using topographic studies method that focuses on investigating the characteristic of highland areas and available rivers systems in Malaysia throughout the map studies. According to the topographic studies, 149 sites were identified in Malaysia, while 30 of existing hydro projects are owned by TNB in Peninsular Malaysia were discovered. Besides exploring the hydro sites potential and project of hydro developments, issues and challenges of hydro development in Malaysia were also emphasized. The proposed suggestions regarding to the issues were presented and discussed in this paper. Overall, this paper summarizes previous research working done on hydro development in Malaysia while in attempt to prove that hydro is a great option as an energy intervention solution in Malaysia due to the geographical conditions based on the topographic studies results.